A Novel Single Source Multiple Output Converter Integrating Buck-Boost and Fly Back Yopology for SMPS Applications - A. Kalirasu (Institute of Advanced Engineering and Science, 2017)
This paper presents a novel single DC input source and multiple DC output suitable for switched mode power supply (SMPS) applications integrating interleaved boost and sepic converter with fly back topology. The proposed converter can be remodeled for any required output voltage power supply without changing hardware structure because wide range of output voltage can be obtained using sepic and boost converters by changing duty cycle command by implementing a simple voltage input pi controller. Conventional fly back topology is added to interleaved circuit to produce desired dc output voltage this voltage can be controlled by choosing turns ratio of fly back transformer. The proposed multi output DC converter is simulated in MATLAB/Simulink environment and results are presented for verifying merits of the converter.